Bat survey of Mount Penrisen and notes on the Rare Kerivoula minuta, Kerivoula intermedia and Hipposideros coxi in Sarawak, Borneo - Jayaraj V.K; Abdullah M.T; Faisal A.A. Khan; Besar Ketol (2006)
In this effort to capture the rare Hipposideros coxi was described from this area, eight mist-nets and three harp-traps were deployed on various locations in the resort for a total of two trapping nights on Mount Penrisen. We recorded 68 individuals from 12 species during the 19 trap-nights including a male Kerivoula minuta which is a new record for Sarawak. In addition to previous sampling, we had recorded 15 copies of bats from two field works on Mount Penrisen. These represent a new distributional records for Mount Penrisen. Comparison with surveys done by several authors at highland areas revealed that higher bat species diversity was observed on Mount Penrisen in terms of number of species. These represent a new distributional records for Mount Penrisen. The targeted species, H.coxi which is endemic to Borneo, was not caught in this survey.Extensive bat surveys should be carried out in the vicinity of the mountain covering much more habitats that are found there. The usage of ultrasonic bat detectors should be incorporated as there is no literature of such method has been employed in the area and microchiropterans of the area still inadequately documented.